Analisis Produktivitas Pekerjaan Pemasangan Dinding Bata Ringan pada Pembangunan Rumah Sakit dengan Metode Work Sampling - Aditya, Bimo Rizky; Fansuri, Muhammad Hamzah; Nuryanto, Fadhil Muhammad (Journal of Research and Inovation in Civil Engineering as Applied Science (RIGID), 2025)
Analyzing labor productivity in construction work is very important as it greatly affects the completion time of construction projects. One of the labor-intensive jobs is the construction of lightweight brick walls. Therefore, productivity analysis is necessary for this job. This study was conducted to measure the productivity value and work utilization rate (LUR) in the National Brain Center Hospital construction project in Jakarta. A sampling method was used with on-site observation over a period of one week. The analysis showed that the average productivity value of workers constructing lightweight brick walls was 9,623 m²/day. The labor utilization rate (LUR) analysis in the construction of lightweight brick walls resulted in a value of 65%, which is higher than 50%, indicating that the construction of lightweight brick walls in this project was effective.